2005
DOI: 10.1158/1078-0432.ccr-04-2703
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Vascular Response to Photodynamic Therapy and the Antivascular Agent 5,6-Dimethylxanthenone-4-Acetic Acid: Implications for Combination Therapy

Abstract: Purpose: Photodynamic therapy (PDT) is a clinically approved treatment for a variety of solid malignancies. 5,6-Dimethylxanthenone-4-acetic acid (DMXAA) is a potent vascular targeting agent that has been shown to be effective against a variety of experimental rodent tumors and xenografts and is currently undergoing clinical evaluation. We have previously reported that the activity of PDT against transplanted mouse tumors is selectively enhanced by DMXAA. In the present study, we investigated the in vivo tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 21 publications
4
44
0
1
Order By: Relevance
“…DMXAA can itself induce synthesis of TNFα in RIF-1 tumors whereas PDT did not and the neutralizing antibodies to TNFα reduced the tumor response to control levels. A subsequent study [51] reported similar results in Balb/c mice with CT26 tumors treated with HPPH-PDT at different fluences and fluence rates combined with DMXAA at two doses. Fig.5 summarizes all cytokine-based combination regimens.…”
Section: The Role Of Cytokines In Pdt Anti-tumor Immunitysupporting
confidence: 54%
“…DMXAA can itself induce synthesis of TNFα in RIF-1 tumors whereas PDT did not and the neutralizing antibodies to TNFα reduced the tumor response to control levels. A subsequent study [51] reported similar results in Balb/c mice with CT26 tumors treated with HPPH-PDT at different fluences and fluence rates combined with DMXAA at two doses. Fig.5 summarizes all cytokine-based combination regimens.…”
Section: The Role Of Cytokines In Pdt Anti-tumor Immunitysupporting
confidence: 54%
“…T (32) and in vivo (33,34). Local depletion of CD4 T cells inside the tumor led to eradication of well established tumors and development of long-term antitumor memory, suggesting that suppression of antitumor immunity by T-regs occurs predominantly at the tumor site and that local reversal of suppression, even late during tumor development, can be an effective treatment (35).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there was no systemic toxicity after combined therapy and no increased normal tissue toxicity compared with PDT alone. Also Seshadri et al 59 tested DMXAA in combination with PDT, but they used as PS, HPPH. Combined therapy at doses 25 mg/kg DMXAA and the HPPH-PDT regimen 48 J/cm 2 resulted in >70% long-term cure rate.…”
Section: Non-specific Methodsmentioning
confidence: 99%